Future Time Perspective and Its Influence on Life Satisfaction through Hope - Kunwijaya, Indrajati; Puji Sugiharto, Dwi Yuwono; Sunawan, Sunawan (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Life satisfaction refers to one’s assessment of life in general. Low life satisfaction leads to negative impacts to a person’s mental health condition. This study identified and analyzed the relationship between the future time perspective and life satisfaction through hope in 567 state high school students in Semarang City. Data were collected using the Satisfaction With Life Scale (SWLS), Synder Hope Scale (SHS) and Future Time Perspective Scale (FTPS). The results of the analysis showed that hope fully mediated the relationship between future time perspective and students’ life satisfaction. This study found that students with good future perspective were satisfied with life because they were able to make route in achieving their goals. The results of this study can be used as insights in counseling intervention and for further research.